Origin of Size Dependency in Coherent-Twin-Propagation-Mediated Tensile Deformation of Noble Metal Nanowires - Seo, Jong-Hyun; Park, Harold S.; Yoo, Youngdong; Seong, Tae-Yeon; Li, Ju; Ahn, Jae-Pyoung; Kim, Bongsoo; Choi, In-Suk (AMER CHEMICAL SOC, 2013)
Researchers have recently discovered ultrastrong and ductile behavior of Au nanowires (NVVs) through long-ranged coherent-twin-propagation. An elusive but fundamentally important question arises whether the size and surface effects impact the twin propagation behavior with a decreasing diameter. In this work, we demonstrate size-dependent strength behavior of ultrastrong and ductile metallic NWs. For Au, Pd, and AuPd NWs, high ductility of about 50% is observed through coherent twin propagation, which occurs by a concurrent reorientation of the bounding surfaces from {111} to {100}. Importantly, the ductility is not reduced with an increase in strength, while the twin propagation stress dramatically increases with decreasing NW diameter from 250 to 40 nm. Furthermore, we find that the power-law exponent describing the twin propagation stress is fundamentally different from the exponent describing the size-dependence of the yield strength. Specifically, the inverse diameter-dependence of the twin propagation stress is directly attributed to surface reorientation, which can be captured by a surface energy differential model. Our work further highlights the fundamental role that surface reorientations play in enhancing the size-dependent mechanical behavior and properties of metal NWs that imply the feasibility of high efficiency mechanical energy storage devices suggested before.
Keywords: SHAPE-MEMORY ALLOYS; GOLD NANOWIRES; AU; ASYMMETRY; STRESS; NITI; PD; NANOWHISKERS; COMPRESSION; PLASTICITY